Production, consumption, and protection: perspectives from North America on the multifunctional transition in rural planning. Issue 3 (2nd July 2016) - Frank, Kathryn I.; Hibbard, Michael
ABSTRACT: Rural areas encompass landscapes that range from peri-urban to very isolated 'deep rural' areas; from rapidly growing high amenity retirement and second home communities to dilapidated near-ghost towns; from those with strong economies in agriculture, natural resource extraction, tourism, and high tech to those with shrinking economies. In addition, such global issues as climate change, food security, and future energy supply have enormous implications for rural places. In these circumstances planning thought and action are confronted – often simultaneously – with physical development – planning for growth and change; production – of traditional agricultural and natural resource outputs but also new outputs such as renewable energy and ecosystem services; and protection – of the natural environment, cultural resources, and social systems. This article draws from the literature and interviews of rural specialists to explore the current tensions between production, consumption, and protection and emerging responses to them, through an exploration of North American rural planning.